TA’SIRU NAMUDAJ AT TA’LIM TA’AWUNI ROUND TABLE ALA NATAAIJ AT TA’ALUM FII MAADATI AL LUGHAH AL ARABIYYAH - Arina Dienana; Isnaeni Khoirul Bariyyah; Bening Anjaswara; Mad ‘Ali (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
Arabic is one of the compulsory subjects in Madrasah Aliyah Negeri 1 Magetan. However, learning Arabic at this school faces challenges, notably students’ limited grasp of the lessons. Furthermore, teachers continue to employ direct methods, resulting in monotonous Arabic language learning activities at these schools, ultimately leading to student disengagement and boredom. Based on the mentioned issues, this research aims to assess the impact of adopting the Round Table Learning model on the Arabic language learning achievements of the 10th-grade students at Madrasah Aliyah Negeri 1 Magetan. This quantitative study uses a true experimental design, specifically a control group design, where the experimental and control groups are randomly selected from the population. The study involves 40 participants, divided equally between the experimental group (20 students) and the control group (20 students), out of a total population of 238 students. Researchers utilized data collection methods, including observation, interviews, tests, and document analysis. The data were analyzed using the t-test (independent samples t-test) due to its normality and homogeneity. The findings from Arabic language learning using the Round Table learning model in class indicate that H0 is rejected and H is accepted; this shows the statistical results of the t-test based on SPSS 25, namely 0.001 < 0.05. Therefore, we conclude that Ho is rejected and Ha is accepted, so it is said that there is a difference between the learning outcomes of Arabic language subjects in the experimental class and the control class.